The 17th International Conference of Students of Systematic Musicology (SysMus24) - Caroline Owen; Saana Sutinen; Juhi Kumari (Music & Science)
The 17th International Conference of Students of Systematic Musicology (SysMus24) was hosted by the Centre of Excellence in Music, Mind, Body, and Brain (CoE MMBB) at the Department of Music, Art, and Culture Studies at the University of Jyväskylä, Finland, from June 8 to 10, 2024. Organized in hybrid format, the conference offered a rich variety of presentations and activities featuring 41 talks, 10 posters, 5 workshops, and a panel discussion, as well as an entertaining program of social events. Keynote talks were given by Minna Huotilainen (Professor of Educational Sciences, Director of the Changing Education master's program and Principal Investigator at the Centre of Excellence in Research on Music, Mind, Body, and Brain at the University of Helsinki, Finland), Tuomas Eerola (Professor in Music Cognition and Director of Research at Durham University, UK) and Isabelle Peretz (Professor of Psychology at the University of Montreal, Canada). This conference report offers an overview of SysMus24, reviewing the topics addressed across the conference, and reflecting on the value and timeliness of the hybrid format and its place within the future of academic conferences.